2017
DOI: 10.1101/194522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Small RNAs are trafficked from the epididymis to developing mammalian sperm

Abstract: SummaryRNAs present in mature mammalian sperm are delivered to the zygote at fertilization, where they have the potential to affect early development. The biogenesis of the small RNA payload of mature sperm is therefore of great interest, as it may be a target of signaling pathways linking paternal conditions to offspring phenotype. Recent studies have suggested the surprising hypothesis that the small RNA payload carried by mature sperm may include RNAs that were not synthesized during testicular spermatogene… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(68 citation statements)
references
References 49 publications
0
68
0
Order By: Relevance
“…Temple-Smith & Bedford, 1980) and eutherian mammals (e.g. Bedford, 1979;Baker et al, 2005;Sullivan & Saez, 2013;Aalberts, Stout, & Stoorvogel, 2014;Skerget et al, 2015;Machtinger, Laurent, & Baccarelli, 2016;Sharma et al, 2018;Nixon et al, 2019a). Although less thoroughly studied, similar changes to sperm may occur within the Wolffian duct of reptiles (e.g.…”
Section: Elements Of the Life History Of Sperm (1) Sperm Maturatmentioning
confidence: 99%
“…Temple-Smith & Bedford, 1980) and eutherian mammals (e.g. Bedford, 1979;Baker et al, 2005;Sullivan & Saez, 2013;Aalberts, Stout, & Stoorvogel, 2014;Skerget et al, 2015;Machtinger, Laurent, & Baccarelli, 2016;Sharma et al, 2018;Nixon et al, 2019a). Although less thoroughly studied, similar changes to sperm may occur within the Wolffian duct of reptiles (e.g.…”
Section: Elements Of the Life History Of Sperm (1) Sperm Maturatmentioning
confidence: 99%
“…At the expense of 'resolution', this strategy maximized the affordability and provided a useful overview for following studies. Given the increasing demands for better resolutions, the progress in the sample preparation for high-throughput studies include the isolation of different epididymal regions (Belleannee et al, 2012;Chu et al, 2015) and the purification of particular cellular components such as epithelial cells (Nixon et al, 2015a), epididymosomes (Hutcheon et al, 2017), spermatozoa (Nixon et al, 2015a(Nixon et al, ,2015bSharma et al, 2016;Chu et al, 2017), and sperm cell parts (Sharma et al, 2018). Among them, spermatozoa can ooze out from the incisions and needle holes made on the epididymis.…”
Section: High-throughput Approaches In Epididymal Sncrna Studiesmentioning
confidence: 99%
“…Additionally, the existence of piRNA sequences in the mature spermatozoa in the cauda epididymis is also quite intriguing. It is gradually revealed that the substantial modifications in the sncRNA content in the spermatozoa is one of the major biological events during their epididymal transit (Nixon et al, 2015b;Chen et al, 2016a;Chu et al, 2017;Sharma et al, 2018). To present a global view of this dramatic sncRNA dynamics during spermatogenesis and sperm maturation in mice, we integrated the small RNA profiles of caput and cauda spermatozoa with those of the testicular spermatogenic cells [data collected from GEO Datasets: GSE24822 (Gan et al, 2011), GSE40397 (Peng et al, 2012) and our own RNA-seq data (GSE122006 and GSE122025)].…”
Section: Progress Over the Past Decadementioning
confidence: 99%
See 2 more Smart Citations